EFEKTIVITAS PELAKSANAAN AKREDITASI SEKOLAH MENENGAH ATAS (STUDI TENTANG EFEKTIVITAS PELAKSANAAN DAN DAMPAK AKREDITASI SEKOLAH TERHADAP UPAYA PENJAMINAN MUTU PENDIDIKAN SMA DI JAWA BARAT) - Hartini, Nani (2010)
he study is entitled "The Effectiveness of the Implementation of Senior High School Accreditation: A study on the implementation and impact of school accreditation towards the effort of improving the quality of High Schools in West Java". The aim of the study is to find the essence of school accreditation in the framework of the national education system, to describe to what extent has Senior High School accreditation been implemented in West Java Province, to describe the profile of the Senior High School accreditation results based on the data in 2007, 2008, and 2009, and to describe the impact of Senior High School accreditation towards the effort in improving the quality of education in West Java, and to formulate the development strategies of the implementation of Senior High School accreditation in West Java. The method in conducting the study is qualitative with a naturalistic approach, the subjects of the study are the Chairman of the Province Accreditation Board of Schools/Madrasah (BAP-S/M), the secretary of BAP S/M, the members of BAP S/M, the assessors, the headmasters of Senior High Schools, and Senior High School teachers in West Java Province who have been chosen through sampling. The findings of the study are (1) the essence of school accreditation in the framework of the national education system is the activities to determine the worthiness of the programs and education units. Based on the results of the study, it can be concluded that the way that Senior High Schools define accreditation in West Java is in the moderate level, this is the result of the lack of understanding of the headmasters, teachers, and other staffs. Accreditation is still considered as an obligation in filling the instruments based on the 8 national education standards, in terms of the function of accreditation, it can be concluded that it has not yet been working optimally. (2) Generally, the implementation of accreditation is in line with the technical policies and guidelines that have been established, however, there are problems in determining the quota of the schools that will be accredited which is not in line with the number of schools (3) From the results of Senior High School accreditation in West Java, it can be concluded that the profile of the accreditation results of Senior High Schools in West Java has gone through an increase in terms of the number of high schools that gained the accreditation of A which is over 75%. In other words, the school ranks cannot yet justify the quality or describe the actual quality of the ranks. The results of accreditation along with all its findings and recommendations are result of careful, credible and reliable work, and are worthy to be considered as reference in developing policies in order to improve the quality of education in Indonesia. (4) The influence of Senior High School accreditation in West Java can be seen from the various activities at schools such as the planning of the school development program although the recommendation of accreditation results have not yet been optimally taken into account, the quality of the students' learning supported by infrastructure that has fulfilled the standards, teachers' performance, in terms of administration and quality, teachers are able to design syllabus and lesson plan, the increase of the society's interest in placing their children in High Schools which are accredited A is felt. (5) An alternative strategy in implementing school accreditation is by giving socialization on the importance of accreditation for schools, training on how to fill accreditation instrument, empowerment of the role of supervisors in the process of filling the instrument, asking assistance from experts (for example, BAN S/M or BAP S/M elements), documenting various school activities both managerial and academic and understand the definition of visitation comprehensively, preparing the set of visitation events neatly and completely, and rehearsing school visitation. Based on the overall description and conclusion above, the recommendations are (1) schools to be aware on the needs of quality which is a requirement and not a coercion or obligation. (2) The government should pay more attention to the findings of BAN S/M in order to design a national education plan based on accreditation results and recommendation. (3) Future researchers should do further study on the implementation of school accreditation in other levels of education.